`Maximum feasible understanding' - lessons from previous wars on poverty - Alcock, Pete (2005)
This article provides a historical analysis of particular policy initiatives undertaken in the US and the UK in the 1960s and 1970s and asks to what extent the lessons from these policy initiatives can be transferred to current policy development in the UK today. The focus of the discussion is local community-based interventions, aimed at combating poverty and exclusion. These are now generally referred to in the UK as Area Based Initiatives (ABIs). - Reproduced.
Keywords: Poverty